Quantitative Analysis of Marketing Strategy Effective Marketing Management Approach - Erislan, Erislan (Jurnal Ilmiah Manajemen Kesatuan, 2023)
In managing marketing strategies, a deep understanding of consumer behavior, market trends and competitive advantages is the main key to achieving success. The importance of effective marketing management is further strengthened by a quantitative approach. This research explores the significance of using a quantitative approach in marketing management and investigates its impact on effectiveness and the challenges it faces. This research uses quantitative methods to evaluate the contribution of statistical approaches and quantitative data analysis in improving the effectiveness of marketing management. Quantitative methods include regression analysis to assess the relationship between the use of a quantitative approach in marketing decision making and company sales growth, as well as ANOVA and correlation analysis to compare the success of marketing strategies. Research findings reveal that quantitative analysis provides valuable insights for designing more effective marketing campaigns and making informed decisions. However, some challenges such as data complexity and resistance to change were observed. Nevertheless, investments in information technology and employee training are proposed as solutions to overcome these obstacles. This research highlights the important role of quantitative approaches in improving marketing management practices.